Variations in the coding of melatonin receptor gene MTNR1A of Iraqi sheep breed: Rahawy, M. A.1; Al-Timimi, I. H.2 , Najwa, Sh. Ahmad3 and Ani A.A4 - A., Rahawy M. (The Iraqi Journal of Veterinary Medicine, 2017)
The aim of the study was found variation of melatonin receptor gene by sequence analysis, investigation in association between MTNR1A polymorphisms with any variation in allele’s frequency of the mutations C606T and G612A of the MTNR1A gene in the Iraqi local sheep lambing out of season. Blood samples were randomly collected from 60 ewes from Agriculture Research-Ruminant Researches Station Breeding Station, Baghdad. Genomic DNA was isolated using a Geneius TM Micro gDNA Extraction Kit. A large fragment of exon 2 of MTNR1A gene was amplified by PCR using specific primer pairs. The PCR product was sequencing 20 samples of MTNR1A gene was performed by National Instrumentation Center for Environmental Management (nicem). The result recorded that sequencing of Ovisaries breed local Iraqi ewes lambing in breeding season genotype rr appeared 100%compatibility with standard, Sequence ID: gb|HQ658147.1|, and have number score (1354) bits there was no any polymorphism in melatonin receptor type 1A (MTNR1A) gene, from 76-808 number of nucleotide from gene of Gene Bank. Sequence product from Iraqi ewes lambing out breeding season have genotype RR appeared 92% compatibility with and Sequence ID: gb|HQ658147.1|, and have number score (896) bits There was high polymorphism in melatonin receptor type 1A gene, from 130-710 number of nucleotide from gene of Gene Bank. The genotype RR that were fifteen only which are identical (G120T, G502C, T512G, T525G, T546A,C567T, T579A, T582C, C605G, A611T, A614T, C620T, G624T, C629T and T642A) that change of amino acid specialty C605G that change Proline to Alanine while four silent mutation (G328C, G499C, C604T and C609A) without amino acid change in spring (out-of-season) breeding in Iraqi local sheep.